Impact of CVOTs in primary and secondary prevention of kidney disease. (November 2019) - De Cosmo, Salvatore; Viazzi, Francesca; Piscitelli, Pamela; Leoncini, Giovanna; Mirijello, Antonio; Bonino, Barbara; Pontremoli, Roberto
Abstract: Type 2 diabetes mellitus is the leading cause of end stage renal disease worldwide. Diabetic kidney disease, whose main clinical manifestations are albuminuria and decline of glomerular filtration rate, affects up to 40% of patients. Sodium Glucose cotransporter-2 inhibitors (SGLT2-is) and Glucagon-like peptide-1 receptor agonists (GLP-1ras) are new classes of anti-hyperglycemic drugs which have demonstrated to improve renal outcome. Renal benefits of both SGLT2-is and GLP-1ras are acknowledged from data of large randomized phase III clinical trials conducted to assess their cardiovascular safety. In this review, we will focus on renal results of major cardiovascular outcome trials, and we will describe direct and indirect mechanisms through which they confer renal protection.